A proposal for a metadata-based framework for interactive GINGA digital TV applications - Silva, Carlos; Machado, Victor; Kuribayashi, Hugo; Jacob Jr, Antonio; Oliveira, Edvar; Seruffo, Marcos; Francês, Carlos; Vijaykumar, Nandamudi; Hirata, Celso (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
The GINGA middleware enables creating applications that are usually known as interactive GINGA applications. The development of these applications shares some requirements that can be explored jointly, such as reusability, standardization, maintainability and extensibility. This work proposes a framework that addresses the shared requirements, beyond integrating other specific-purposes frameworks. The metadata-based framework approach is used to provide the declarative configuration. This framework extends functionality of some pre-existing components of GINGA and allows easier implementation of new components.